THE FEMINIST MOVEMENT: FROM NECESSITY TO AVANGARDE - Valentina Tănase (Romanian Journal of Historical Studies)
This study is dedicated to the overall approach of the feminist evolution issue or the fight for women’s rights. In this regard, if in the middle of the 19th century, when we can already talk about such a feminist movement, first we must have in mind the incentive of economic, social or political necessities, today, almost the whole issue regarding these rights is covered by legislation, therefore this movement can no longer be regarded as a necessity. This article tells a short history of feminism, both Western and Romanian, as an integral part of the European one. As the feminist movement first manifested itself by publishing some works in which they protested against woman’s inferiority, these works are mentioned in this article